Pembentukan Program Pengajian Ibu-Ibu sebagai Media Pembelajaran Iqro’ dan Al-Qur’an di Desa Bendungan, Kecamatan Cawas, Kabupaten Klaten - Habib Khoirul Umam; Isti Azizah; Dhiliya Aulia Karin; Abilda Inova Yulia Fitri; Indah Anggun Listina; Muhammad Faisal Faqikh; Diah Novita Fardani (CV. ITTC INDONESIA, 2026)
This community service activity aimed to re-establish the women’s Islamic study group in RW 07, Bendungan Village, Cawas District, Klaten Regency, as a medium for teaching Iqro’ and the Qur’an. The program was implemented through regular assistance three times a week using the private-tilawati and sorogan methods according to the participants’ abilities. The participants consisted of 13 women from the Iqro’ and Qur’an groups. The results showed improvements in reading ability, reading fluency, and understanding of basic tajwid. The activity also increased the participants’ self-confidence, learning motivation, and active participation. The re-establishment of the management structure and study schedule indicates that the program can be continued independently by the community. Therefore, this women’s study group program contributed to improving Qur’anic learning and strengthening religious activities within the community.